Hubungan Kelainan Letak dan Paritas dengan Kejadian Ketuban Pecah Dini di Rumah Sakit Harapan Bunda Kota Batam Tahun 2024 - Vyona Wifiarni Putri; Desi Pramita Sari; Resi Novia (Jurnal Kesehatan Amanah, 2025)
Premature Rupture of Membranes (PROM)s a condition where the amniotic sac breaks before labor begins. This can occurn full-term pregnancies (≥37 weeks) or preterm pregnancies (<37 weeks), whichs also known as preterm PROM. PROMs one of the main risk factors for complicationsn both the mother and the baby, during and after childbirth. Therefore,tsmportant todentify the factors associated with the occurrence of PROM. This study aims to examine the relationship between fetal malpresentation and parity with thencidence of PROM at Harapan Bunda Hospitaln Batam Cityn 2024. The research used a quantitative approach with a retrospective case - control design. A total of 42 mothersn labor were selected using purposive sampling based on specific criteria. Analysis using the chi-square test showed a p-value of 0.000 (<0.05),ndicating a significant relationship between fetal malpresentation and maternal parity with the occurrence of PROM.t can be concluded that abnormal fetal position and the number of previous births (parity) are strongly related to the risk of premature rupture of membranes among mothers giving birth at Harapan Bunda Hospital.